Effect of Bottom Tuyere Arrangement Based on Impact Cavity Morphology on Kinetic Behavior of Molten Bath in Converter. Issue 1 (17th October 2022) - Sun, Jiankun; Zhang, Jiangshan; Jiang, Rui; Feng, Xiaoming; Liu, Qing
Abstract : The hydrodynamic interaction between the top blowing supersonic jet and the bottom plume significantly affects the kinetic behavior of the molten bath in the steelmaking converter. Herein, considering the influence of cavity morphology, four bottom tuyere arrangement cases are designed, and their effects on the gas–slag–metal interface characteristics, dynamic and mixing characteristics of molten bath, and abrasion characteristics of refractory lining are numerically studied. The results show that the gas–slag–metal interaction is more violent in the corner region of scattered cavities, with higher velocity, turbulent kinetic energy, and splashing. Arranging the tuyeres in the corner region of scattered cavities would exacerbate the nonuniformity of velocity and splashing, resulting in a large dead zone and high kinetic energy dissipation, which is not favorable to the efficient stirring and mixing of the molten bath. In contrast, arranging the tuyeres in the region of the extension line between the center of the molten bath and the center of scattered cavities may effectively enhance the relevant flow parameters. Furthermore, when the tuyeres are arranged in the corner region of scattered cavities, the bottom abrasion is more serious than that in other regions. Abstract : The scattered cavities morphology significantly affects the dynamic characteristics of the molten bath. Based on this, arranging the bottom tuyeres in Region B Will exacerbate the nonuniformity of velocity and splashing, resulting in a large dead zone and high kinetic energy dissipation. In contrast, arranging the bottom tuyeres in Region A will effectively improve the stirring and mixing of the molten bath.